HISTORY AND CARTOGRAPHY: MEDIEVAL ISLAMIC AND CHRISTIAN CARTOGRAPHY AND THE CLASH OF CIVILISATIONS - Sarkytkan, Қ.; Amirbekova, С.К. (Journal of Oriental Studies, 2025)
History and geography are fundamental concepts that represent time and space. From the intersection of these two philosophical concepts, human civilisations emerged. Civilisation is a deepened and widespread level of culture. Civilisations have left us historical maps as a cultural and scientific heritage. These maps are not only valuable sources of the past but also a reflection of spatial perception. With the development of human society, map-making evolved into an independent scientific field, forming the basis of cartography as a science. Initially considered a branch of geography, cartography has, under the influence of scientific and technical progress, become a comprehensive field of study today. The purpose of this research compares the cartographic traditions of the medieval Islamic world and the Christian world, analysing their worldview and cultural characteristics. This comparison allows us to evaluate not only the historical roles of these two major civilisations but also their level of participation in today's global processes. In particular, the issue of the contemporary Muslim world’s place in the era of globalisation and its capacity to confront geopolitical challenges is of significant relevance. Given the scope and significance of the article, as well as its objectives and tasks, we apply the historical-genetic method. This allows us to study the origins of cartographic science, its evolutionary development, and the emergence of cartographic traditions among different civilisations. In addition, through comparative and textual analysis methods, we examine the ideological and scientific content of medieval sources, maps, and their descriptions. By employing an interdisciplinary approach, we can comprehensively explore this issue, which lies at the intersection of several fields such as geography, history, cultural studies, philosophy, and political science. These methods enable us to view the map not merely as a geographic tool, but also as a cultural and cognitive phenomenon. Based on scientific research and historical records, it is evident that the Islamic world achieved significant advancements in science and education throughout the development of human civilisation. During the medieval period, the Muslim world made remarkable progress in fields such as medicine, mathematics, astronomy, philosophy, and other sciences, playing a crucial role in shaping subsequent civilisations. However, due to periods of political instability, cultural transformations, and economic and social crises, the Islamic world’s scientific leadership declined, and its prominence on the historical stage diminished. In the current context of globalisation, there is an increasing dependency of the Muslim world on global geopolitical and geoeconomic centres. Evaluating this situation solely from a Eurocentric perspective would be a stance far removed from historical fairness. Taking into account the cyclical nature of historical and civilisational development, it can be reasoned that global dominance and civilisation are not eternal; each era is marked by its own distinctive features, and scientific, technological, and cultural progress unfolds in stages. Therefore, the current global order is also subject to change, and within these changes lies the potential for the Islamic world to experience a revival and to restore its scientific capacity. In particular, when addressing the issue of conflicts between civilisations, it is essential to maintain a balanced perspective that respects both change and historical realities. Keywords: cartography, comparative analysis of cultures, historical maps, medieval Islamic cartography, Christian cartography, clash of civilisations, globalisation and geopolitics.